Developing an Operational Guideline as a Value-Based Decision-Support Mechanism for RICEFW Backlog Prioritization in SAP S/4HANA Implementation Using VFT and Smart at PT Bukit Asam - Istanto, Dimas; Hermawan, Pri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research is motivated by the need, during PT Bukit Asam’s (PTBA) 1ERP SAP S/4HANA implementation, to prioritise a cross-module RICEFW backlog under limited time and delivery-capacity constraints. In the observed condition, prioritization tends to be influenced by short-term urgency and unit-level preferences because a structured, transparent, feasible, and documented value-based decision-support mechanism is not yet available to guide cross-functional discussion. Therefore, this study develops a documented value-based decision-support mechanism that can provide a shared evaluation standard and support consistent prioritization and trade-off deliberation across functions. To develop the required mechanism, this study follows the conceptual framework and operationalises it into three sequential stages: Problem Structuring and Criteria Design, Assessment and Initial prioritization, and Priority Shortlist and Robustness Review. The research is conducted as a value-based MCDA single-case study in the context of PTBA’s SAP S/4HANA implementation. Value-Focused Thinking (VFT) is used to derive decision objectives and translate them into a fixed criteria set (C1–C5) with clear definitions and 1–5 scoring rubrics. Cross-functional assessments are collected using the rubrics and aggregated using a SMART-type additive value model to produce a baseline ranking and an initial priority shortlist. Robustness is then examined by applying discrete weight profiles to assess the stability of the resulting ranking and shortlist. The mechanism is documented as an Operational Guideline that consolidates the evaluation standard, prioritization results, and a decision trail summary as a practical input for cross-functional decision meetings. The outputs of this study include a fixed criteria set with scoring rubrics, a baseline ranking of 27 predefined RICEFW groupings, and a provisional Top-15 priority shortlist intended as discussion material for release planning. Across the tested discrete weight profiles, the Top-15 overlap is 14 out of 15 under Weight Profile A and 14 out of 15 under Weight Profile B; in addition, 13 groupings form a stable core that consistently remains in the shortlist across all tested profiles. Weight Profile C is identical to the baseline and is included as a replication check rather than a preference-shift case. In conclusion, these outputs are compiled and documented into an Operational Guideline as a value-based decision-support mechanism that provides a shared evaluation standard, supports consistent cross-functional prioritization discussions, and improves traceability through documented decision inputs.